2021
DOI: 10.3390/en14175522
|View full text |Cite
|
Sign up to set email alerts
|

Non-Destructive Acoustical Rock Bolt Testing System with Intelligent Filtering in Salt Mine ‘Wieliczka’

Abstract: This article presents the application of a self-excited acoustic SAS system for non-destructive testing (NDT) for roof-bolt housings in laboratory and real mine conditions. The proposed system with a filtering mechanism was applied to the J64-27 composite anchors. The conducted tests allowed successful confirmation of the usefulness of the system in the detection of rod defects, damage of the mechanism coupling the anchor to the rock mass and testing of the stress state of the anchor itself. The proposed filte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…It was previously shown that the modified UPV of concrete with a steel bar is in good agreement with the measured UPV of plain concrete for the transducer spacing from 100 mm to 500 mm. Thus, the modified UPV, ranging from 100 mm to 500 mm, can be used to determine the average UPV and hence to determine the actual compressive strength of concrete using Equation (14). According to Table 4, the actual average compressive strength is 27.0 MPa, considering six cubes.…”
Section: Compressive Strengthmentioning
confidence: 99%
See 1 more Smart Citation
“…It was previously shown that the modified UPV of concrete with a steel bar is in good agreement with the measured UPV of plain concrete for the transducer spacing from 100 mm to 500 mm. Thus, the modified UPV, ranging from 100 mm to 500 mm, can be used to determine the average UPV and hence to determine the actual compressive strength of concrete using Equation (14). According to Table 4, the actual average compressive strength is 27.0 MPa, considering six cubes.…”
Section: Compressive Strengthmentioning
confidence: 99%
“…Therefore, the problem was raised, and this project is going to solve the contradiction of avoiding the use of the ultrasonic pulse velocity method in concrete structures if a single reinforced bar is present under the condition of indirect transmission. One of the methods of testing both steel and plastic bars is the self-excited acoustical system [13,14].…”
Section: Introductionmentioning
confidence: 99%